Fatalne zauroczenie (Wiktor Pielewin, Miłość do trzech Zuckerbrinów) - Zywert, Aleksandra (Studia Rossica Posnaniensia, 2020)
The aim of this paper is to analyze an increasingly dangerous phenomenon in modern times – the Internet addiction – in the context of contemporary Russian literature. It seems that in this light, the work of Viktor Pelevin can serve as a perfect example of a literary voice in the discussion about the condition of the modern world. The present paper uses the findings of modern technology experts (e.g. Clifford Stoll), philosophers, and sociologists (e.g. Jean Baudrillard, Kazimierz Krzysztofek). In Viktor Pelevin’s novel entitled Love for Three Zuckerbrins (Любовь к трeм цукербринам, 2014) the author continues his analysis of the problem, already marked in The Helmet of Horror (Шлем ужаса: Креатифф о Тесее и Минотавре, 2005), centered on the impact of the development of the latest technologies on human beings. While in the author’s earlier works this issue remained in the sphere of predictions and guesses, here it is unequivocally resolved to the detriment of the human individual. By touching upon the question of popular games for people, Pelevin shows their real role – playing with people. In this context the abovementioned attraction to simple entertainment has irreversible effects – a win in an Internet game means a failure in real life. While advocating unequivocally on the side of the opponents of the adulation for cyberspace, Pelevin points out that a complete unification with it will lead to the end of humanity.